How would a slowdown in the People's Republic of China affect its trading partners? - Willem Thorbecke (Elsevier, 2021)
The People's Republic of China (PRC) has become an important importer for many countries. This paper investigates how turbulence in the PRC can spill over to trading partners through the trade channel. Exports from several East and Southeast Asian countries to the PRC exceed 10% of their GDPs. To shed light on countries’ exposures to the PRC, this paper estimates a gravity model. The results indicate that Taipei, China and the Association of Southeast Asian Nations are exposed to the PRC because they produce goods for the Chinese market and exposed to advanced economies because they ship parts and components to the PRC for processing and re-export to the West. South Korea is more exposed to a slowdown in advanced economies that purchase processed exports from the PRC than to a slowdown in the PRC. Major commodity exporters such as Australia, Brazil, Indonesia, and Saudi Arabia and exporters of sophisticated consumption and capital goods such as Germany and Switzerland are exposed to a slowdown in the Chinese domestic market. This paper also estimates import elasticities for the PRC. The results indicate that imports for processing into the PRC are closely linked to processed exports from China to the rest of the world and that ordinary imports are closely linked to Chinese GDP. The renminbi exerts only a weak impact on imports, however. The paper concludes by recommending that firms and countries diversify their export base and their trading partners to reduce their exposures to the PRC and to advanced economies.